Transposable elements are associated with genome-specific gene expression in bread wheat - Bariah, Inbar; Gribun, Liel; Kashkush, Khalil (Frontiers in Plant Science, 2023)
Recent studies in wheat emphasized the importance of TEs, which occupy ~85% of the wheat genome, as a major source of intraspecific genetic variation due to their recent activity and involvement in genomic rearrangements. The contribution of TEs to structural and functional variations in bread wheat genes is not fully understood. Here, publicly available RNA-Seq databases of bread wheat were integrated to identify TE insertions within gene bodies (exons\ introns) and assess the impact of TE insertions on gene expression variations of homoeologs gene groups. Overall, 70,818 homoeologs genes were analyzed: 55,170 genes appeared in each one of the three subgenomes (termed ABD), named triads; 12,640 genes appeared in two of the three subgenomes (in A and B only, termed AB; or in A and D only, termed AD; or in B and D only, termed BD;), named dyads; and 3,008 genes underwent duplication in one of the three subgenomes (two copies in: subgenome A, termed AABD; subgenome B, termed ABBD; or subgenome D, termed ABDD), named tetrads. To this end, we found that ~36% of the 70,818 genes contained at least one TE insertion within the gene body, mostly in triads. Analysis of 14,258 triads revealed that the presence of TE insertion in at least one of the triad genes (7,439 triads) was associated with balanced expression (similar expression levels) between the homoeolog genes. TE insertions within the exon or in the untranslated regions (UTRs) of one or more of the homoeologs in a triad were significantly associated with homoeolog expression bias. Furthermore, we found a statistically significant correlation between the presence\absence of TEs insertions belonging to six TE superfamilies and 17 TE subfamilies and the suppression of a single homoeolog gene. A significant association was observed between the presence of TE insertions from specific superfamilies and the expression of genes that are associated with biotic and abiotic stress responses. Our data strongly indicate that TEs might play a prominent role in controlling gene expression in a genome-specific manner in bread wheat.